4-Ethylphenol, A Volatile Organic Compound Produced by Disease-Resistant Soybean, Is a Potential Botanical Agrochemical Against Oomycetes - Ge, Ting; Gao, Wenteng; Liang, Changhui; Han, Chao; Wang, Yong; Xu, Qian; Wang, Qunqing (Frontiers in Plant Science, 2021)
Oomycetes, represented by Phytophthora, are seriously harmful to agricultural production, resulting in a decline in grain quality and agricultural products and causing great economic losses. Integrated management of oomycete diseases is becoming more challenging, and plant derivatives represent effective alternatives to synthetic chemicals as novel crop protection solutions. Biologically active secondary metabolites are rapidly synthesized and released by plants in response to biotic stress caused by herbivores or insects, as well as pathogens. Here, we identified groups of volatile organic compounds (VOCs) from soybean plants inoculated with Phytophthora sojae, the causal agent of soybean root rot. 4-Ethylphenol was present among the identified VOCs and was induced in the incompatible interaction. 4-Ethylphenol inhibited the growth of P. sojae and Phytophthora nicotianae and had toxicity to sporangia formation and zoospore germination by destroying the pathogen cell membrane; it had a good control effect on soybean root rot and tobacco black shank in the safe concentration range. Furthermore, 4-Ethylphenol had a potent antifungal activity against three soil-borne phytopathogenic fungi, Rhizoctonia solani, Fusarium graminearum, and Gaeumannomyces graminis var tritici, and four forma specialis of Fusarium oxysporum, which suggest a potential to be an eco-friendly biological control agent.